Globalization and Capitalist Geopolitics : Sovereignty and state power in a multipolar world - Woodley, Daniel (Taylor & Francis)
In a period of increasing geopolitical insecurity and economic instability this title provides an authoritative yet accessible commentary on debates on capitalism and globalization in the wake of the financial crisis.
English
Keywords: Globalization; Economics; International Relations; Globalization; Capitalism; China; Geopolitics; Western world